Filosof dan Temuan Kesehatan Islam - Fitri Idani (Raudhatun Najah Publisher, 2024)
Ideally, the concept of Islamic health should be understood as a comprehensive system of thought rooted in divine revelation and strengthened by the intellectual contributions of Muslim philosophers. This concept is expected to integrate physical, mental, and spiritual dimensions of human existence in a balanced manner. However, in reality, contemporary discussions on Islamic health tend to be fragmented, focusing mainly on normative-theological or medical aspects, while the philosophical foundations developed by Muslim philosophers receive limited attention. This condition creates a conceptual gap between Islamic philosophical thought and Islamic health findings. Therefore, this study aims to analyze the views of Muslim philosophers regarding the body, soul, and health, and to examine their relevance to the concept of Islamic health. This research employs a library research method with a qualitative approach, using philosophical-normative and historical-conceptual analysis of classical works and contemporary literature. The findings indicate that Muslim philosophers provide a strong conceptual foundation for Islamic health by emphasizing the balance between body and soul within an ethical and spiritual framework. The integration of these philosophical perspectives demonstrates that Islamic health is holistic, rational, and remains relevant in addressing contemporary health challenges.